Teratogenic Effects of Durian Fruit (Durio Zibethinus Murr) on White Mice Fetus (Mus musculus L) - Rusdi, Mesa Sukmadani; Efendi, M. Rifqi; Hilma, Hafizhatul (Pharmauho: Jurnal Farmasi, Sains, dan Kesehatan, 2021)
Durian (Durio zibethinus L.) is one of the most consumed and liked fruit in Indonesia, but there was no evidence about the safety of consuming durian during pregnancy. This study was determine the level of safety of durian fruit consumption during pregnancy by conducted teratogenicity test of durian fruit (Durio zibethinus Linn) on fetuses of white mice (Mus musculus L). Teratogenicity test was conducted in vivo, by step: preparation of experimental animal, observation during administration, laparotomy, fixation and observation of morphological defects. Data were analyzed using Analysis of Variance (ANOVA). If the results were significant (P < 0.05), the analysis was continued using Duncan Multiple Range Test. Administration durian during pregnancy did not affects the bodyweight of the mice (P > 0,05), but significantly influences the number of fetuses (P < 0,05) and its body weight (P < 0,05). Consumption of durian during pregnancy is safe in 32,5 mg / KgBW, but it has the potential teratogenic in 65 mg / KgBW and 97,5 mg/KgBW groups. Teratogen effects that were found in several fetuses were underweight, dead, hemorrhage, maternal death and there were resorption sites.